Analysis of Moral and Spiritual Development in Vocational High School Students - Wiwin Nur Hidayah; Cucuk Wawan Budiyanto; Yuliyani Siyamtiningtyas (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2024)
Moral and spiritual education is very important in preparing the character of quality students to enter the world of work. However, currently, there is a decline in the morale and spirituality of students, one of which is at Vocational High Schools (SMK). This research aims to determine the level of moral and spiritual development of students and how schools participate in developing moral and spiritual values. This research method uses a descriptive method with a qualitative approach, data collection through observation, and interviews with participants who have been selected through a purposive sampling technique. Based on the research results, show that students in vocational high schools have variations in moral development, which reflects individual differences in understanding and internalizing moral values. The educational approach in vocational high schools is intended to support spiritual development by allowing students to explore their values and beliefs, providing space for reflection, and encouraging them to participate in spiritual practices.Keywords: Moral, Spiritual, Vocational High Schools